Criminal implications of giving false information by employees (analysis of decision number 16/Pid.B/2024/pn kbu) - Yurita, Irma; Dinata, M. Ruhly Kesuma; Abduh, Salis M (Journal of Law Science, 2025)
Providing false information by employees is an action that can have significant legal impacts, both for the individual concerned and the institution where they work. This research aims to analyze the criminal implications of acts of false information carried out by employees, with a focus on the application of the evidentiary system in proving the elements of the criminal act of false information in accordance with Article 242 of the Criminal Code and the provisions of the criminal law that regulate the prosecution and qualification of such actions. In this research, the method used is normative juridical analysis with a case study approach. The results of the research show that the application of the evidentiary system in cases of false statements involves witness statements, evidence, and the defendant's confession which support each other to prove that the information given is not true. The conclusion of this research confirms that acts of false information by employees not only harm the company but can also damage public trust in institutions. Therefore, it is important to implement a strict evidentiary system and provide strict sanctions for such actions to maintain justice and legal integrity. It is hoped that this research can contribute to the development of criminal law in Indonesia, especially in handling cases of false statements involving employees